2017
DOI: 10.18517/ijaseit.7.3.1775
|View full text |Cite
|
Sign up to set email alerts
|

Growth Response of Two Varieties Chrysanthemum (Chrysanthemum sp.) On Some Media Composition

Abstract: Chrysanthemum is one type of ornamental plants flowers are very popular and have a relatively high economic value in Indonesia and have good marketing prospects. Requests cut flowers, and potted chrysanthemum plants are increasing from year to year, in line with improving standards of living. This study aims to obtain best medium composition on the growth of two varieties of chrysanthemum. The research was conducted in greenhouses West Sumatera Institute Assessment and Agricultural Technology in Sukarami Solok… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 16 publications
0
7
0
1
Order By: Relevance
“…Photosynthate from photosynthesis is translocated to tubers. The leaf area is greater, resulting in more photosynthesis and a higher resulting fresh weight [23].…”
Section: Number Of Tuber Per Plantmentioning
confidence: 99%
“…Photosynthate from photosynthesis is translocated to tubers. The leaf area is greater, resulting in more photosynthesis and a higher resulting fresh weight [23].…”
Section: Number Of Tuber Per Plantmentioning
confidence: 99%
“…Warnita et al [15] reported that a high N content would increase the size and number of leaf cells, thus increasing the number of leaves. This is in line with the statement of Aisyah et al [16], nitrogen has a function, one of which is as a constituent of chlorophyll, when leaves have a chlorophyll content that is not optimal, it can slow down leaf propagation and vice versa.…”
Section: Plant Height Number Of Leaves and Number Of Branchesmentioning
confidence: 99%
“…The number of leaves with a lot of leaf area is larger so that photosynthesis is more and will increase the resulting fresh weight higher [15]. According to Santi's research [20], the application of manure has an effect on plant height, number of leaves, number of fruits and fruit weight of tomato plants.…”
Section: Number Of Pods Fresh Weight Of Pods Per Plant and Per Hectarementioning
confidence: 99%
“…Bila terlalu lembab, anthurium lebih mudah terserang hama penyakit terutama pada bagian akar dan batang (Budhiprawira dan Lestari (2007). Kemudian Warnita et al (2017) menyatakan media tanam anthurium terdiri atas tanah, pasir, dan pupuk kandang dicampur dengan perbandingan 1:1:1 (v/v).…”
Section: Pendahuluanunclassified